The consent in sex trafficking under the hammer of the Judiciary: judicial practices and discourses - Garbellini Filho, Luiz Henrique; Borges, Paulo Cesar Correa [UNESP] (Univ Estado Rio De Janeiro, Fac Direito, 2022)
This paper aims to analyze the judicial response on consent to sex trafficking. The qualitative analysis falls on the judicial practices and discourses of the Court's judges in seven (07) judgments of the Tribunal Regional Federal da 3 Regiao as elements for problematizing the relation between punitive power and gender from the theoretical -methodological arsenal of Feminist Criminology and Critical Discourse Analysis. We sustain that, in decisions after 2016, the judges have (i) broked with the categorization, standardized portraits and moral panics about sex trafficking, as well as (ii) modified the understanding about consent, which became relevant for a configuration of crime. We argue that the judges can create new standards of anti-discriminatory and non -generalizing judicial understandings, however, they fail to develop an effective feminist legal project.
Keywords: Law; Gender; Consent